A high-performance photoelectrochemical sensor for the specific detection of H2O2 and glucose based on an organic conjugated microporous polymer. Issue 46 (17th November 2021) - Sun, Qiqi; Liu, Qi; Gao, Wen; Xing, Chuanwang; Shen, Jingshun; Liu, Xue; Kong, Xia; Li, Xiyou; Zhang, Yuexing; Chen, Yanli
Abstract : A photoelectrochemical sensor for H2 O2 and glucose with remarkable specificity is developed based on a unique periodic D–A type PorPc-CMP hollow tube. Abstract : Cathodic photoelectrochemical (PEC) biosensors are one of ideal systems for sensing applications owing to their advantages in the low-cost, simplicity of the detection and miniaturization of the sensors with high sensitivity and specificity. Herein, a high-performance PEC sensor based on a 2D porphyrin–phthalocyanine conjugated microporous polymer (PorPc-CMP) is reported for the specific detection of H2 O2 and glucose in the wide linear ranges of 0.05–100 and 0.05–5000 μM with an ultra-low limit of detection (LOD) of 13 and 27 nM, respectively. All of them achieved the best levels, when compared to H2 O2 and glucose tetrapyrrole-based photoelectrochemical sensors reported so far. After a comparative analysis on the morphology, optical–electrical properties and partial charge density plots by DFT calculations for the PorPc-CMP and its analogues (PorPor-CMP and PcPc-CMP), it is revealed that the high PEC-sensing performance of PorPc-CMP is largely related to the synergistic effect of unique multi-channel D–A structure and elaborate hollow tube-like morphology, which leads to the effective charge separation, enhanced charge transportability and high utilization of light irradiation. Furthermore, good accuracy of the PorPc-CMP PEC sensor was demonstrated in real sample analysis of H2 O2 disinfectant and human serum samples.